Marine and Terrestrial Organic Ice-Nucleating Particles in Pristine Marine to Continentally Influenced Northeast Atlantic Air Masses - McCluskey, Christina S.; Ovadnevaite, Jurgita; Rinaldi, Matteo; Atkinson, James; Belosi, Franco; Ceburnis, Darius; Marullo, Salvatore; Hill, Thomas C.J.; Lohmann, Ulrike; Kanji, Zamin A; id_orcid:0 000-0001-8610-3921; O'Dowd, Colin; et al. (Journal of Geophysical Research: Atmospheres, 2018)
ISSN:0148-0227 ISSN:2169-897X